2008
DOI: 10.1111/j.1464-5491.2007.02339.x
|View full text |Cite
|
Sign up to set email alerts
|

Survey of glargine use in 115 pregnant women with Type 1 diabetes

Abstract: The use of glargine in Type 1 diabetes during pregnancy was not associated with any unexpected adverse maternal or fetal outcome in this study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
1
1

Year Published

2010
2010
2015
2015

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(30 citation statements)
references
References 19 publications
0
28
1
1
Order By: Relevance
“…70 Several small studies and a meta-analysis have investigated both neonatal and maternal outcomes following glargine use in pregnancy. [71][72][73][74] All have reported no increased fetal or maternal adverse events when glycemic control was obtained using glargine compared with NPH insulin.…”
Section: Pregnancymentioning
confidence: 95%
“…70 Several small studies and a meta-analysis have investigated both neonatal and maternal outcomes following glargine use in pregnancy. [71][72][73][74] All have reported no increased fetal or maternal adverse events when glycemic control was obtained using glargine compared with NPH insulin.…”
Section: Pregnancymentioning
confidence: 95%
“…No large randomized clinical trials with insulin glargine used during pregnancy have been done up to now (21). It was also proven that insulin glargine does not cross the placenta (39), and many studies with small number of patients have shown the safety and efficacy of its use in pregnancy (40)(41)(42)(43)(44)(45)(46)(47)(48)(49)(50)(51)(52)(53)(54)56). Negrato and cols.…”
Section: Insulin Glarginementioning
confidence: 99%
“…Severe maternal hypoglycemia, defined as requiring third-party assistance, was reported in 22%. In terms of neonatal outcomes, 47% (50/114) of neonates experienced hypoglycemia, mean birth weight was 3500±600g, and three had congenital abnormalities [43].…”
Section: Long Acting Insulin Analoguesmentioning
confidence: 99%
“…In 2008, Gallen et al [43] published an uncontrolled prospective audit of 115 pregnant women with T1DM treated with glargine. Of these, 69% were treated with glargine during the preconception period.…”
Section: Long Acting Insulin Analoguesmentioning
confidence: 99%